Skeletal muscle heat shock protein 60 increases after endurance training in mice and induces peroxisome proliferation-activated receptor-γ coactivator-1 α1 expression - Sangiorgi, Claudia; Barone, Rosario; Macaluso, Filippo; Marino Gammazza, Antonella; Campanella, Claudia; D’Amico, Daniela; Moresi, Viviana; Coletti, Dario; Adamo, Sergio; Cappello, Francesco; et al. (Italian Journal of Anatomy and Embryology, 2015)
Heat shock protein (Hsp60) is a mitochondrial chaperonin whose unconventional cellular localizations and functions are discovered day by day. In the present study, the levels of Hsp60 in fibres of the soleus muscle and its correlation to the expression of four isoforms of peroxisome proliferation-activated receptor-γ (PPAR-γ) coactivator-1α (PGC1α) were investigated in 72 young (7-weeks old) healthy male mice (BALB/c AnNHsd) at baseline and after completing a 6-week endurance training program. The mice were assigned to one of the two experimental groups: SED (sedentary) or TR (trained). Short-term overexpression of hsp60, achieved by in vitro plasmid transfection, was then performed to determine whether this chaperonin could have a role in the activation of the expression levels of PGC-1α isoforms. The levels of Hsp60 protein were fibre-type specific in the posterior muscles at baseline, and endurance training increased its content in type I muscle fibers. Concomitantly with the increased levels of Hsp60 released in the blood stream of trained mice, mitochondrial copy number and the expression of three isoforms of PGC-1α increased. Overexpressing hsp60 in cultured myoblasts induced only the expression of PGC-1 α1, letting us suppose a direct correlation between Hsp60 overexpression and PGC-1 α1 activation. Overall, these results suggest that during endurance training Hsp60 is upregulated and activates the mitochondrial biogenesis pathway, probably as a response to the oxidative stress induced by exercise. This study reveals a molecular response of skeletal muscle to a mechanical stress induced by training which involves the molecular chaperonin Hsp60 and the transcriptional co-activator PGC-1 α1. The role of these proteins in aerobic adaptation and pathological conditions as cancer cachexia warrants further investigations.